Hepatoprotective activity of Sri Lankan black tea (Camellia sinensis) in rats - Rathnasooriya, W.D.; Fernando, T.S.P. (My University, 2010)
S c i c n l i l l c i n f o r m a t i o n on h c p a t o p r o l c c t i v e p o t e n t i a l o f b l a c k l e a o\' Camellia sinensis (L) O . K. L i n t / (F-'amilx'; T h e a c c a c ) is scurcc, I h i s >iud\ ihcix'l'orc- i n \ c s t i g a t c d \hc J i c p a l o p r o i c c t i v c a c t i \ i t y o f b l a c k tea b r ew (BTB) o f T. sinensis (using S r i L.ankan h i g h g r o w n D u s i grade Ni>: ). in rat c a r b o n t e t r a c h l o r i d e h e p a t i c l e s i o n in o d e I w i l h t w o oral closes (5(11 and 1336 nig/nil g i v e n o r t i lK Tor 3 con->eL-uii \ i.ia\. I he rc'^iik showed dial both doses s i g n i f i c a n t l v ' ( l ' < (1.05) r e d a c e d S G P T le\el but not S G ( ) T le\et o n da\ 4 a n d 7 post treatment. Il i ^ c o n c l u d e d hca\ c o n ^ u m p i i o n o f B I B o i ' C siiwnsi.s can i n d u c e m i l d l i e p a t o p r o t e e l i v c a c t i o n w i t h a q u i c k onset.